Counselling Survivors of Traumatic Brain Injury - Lewington, Philippa J. (Canadian Journal of Counselling and Psychotherapy, 1993)
Counselling for survivors of traumatic brain injury is gradually gaining recognition and acceptance. The objectives of this article are to identify the reasons for the increasing use of psychotherapeutic intervention for brain dysfunctional adults; to explore the complexities of working with this special population; and to highlight the needs and goals typically encountered in the therapeutic session. Knowledge, flexibility, and creativity are required to develop novel ways of healing the shattered sense of self, eliciting a new and integrated self and finding purpose and meaning after traumatic brain injury. Modifications to traditional counselling approaches are discussed.